International Law Study on the Execution of Mortgage Guarantee Assets Located Outside Indonesia. - Kadafi, Syahril; Adjie, Habib (Jurnal Hukum dan Keadilan, 2025)
Mortgage guarantee is a form of material security regulated in Indonesian civil law. Provisions regarding mortgage guarantees can be found in Articles 1162 to 1232 of the Civil Code (Civil Code). These articles include general provisions to special rules related to mortgage guarantees. In addition, the Commercial Code (KUHD) also regulates certain aspects of mortgage collateral, especially in Articles 314 to 316, which highlight objects that can be used as collateral for mortgages in business transactions. In addition to these regulations, Law Number 17 of 2018 concerning Notary Services also has relevance in regulating mortgage guarantees, especially in relation to the process of recording and legal validation of mortgage agreements. This journal article discusses international legal studies related to the execution of mortgage-backed assets located outside the territory of Indonesia. The main focus of this study is to analyze how international legal principles can be applied in the context of cross-border mortgage guarantee dispute resolution. With a legal reconstruction approach, this study aims to provide an in-depth understanding of the relationship between international law and the implementation of the right of guarantee on a global scale